UJI EFEKTIVITAS ANTIBAKTERI PERASAN SEGAR DAN SERBUK UMBI BAWANG PUTIH (Allium sativum L.) TERHADAP BAKTERI Salmonella typhi - Komala, Oom; Asmara, Herra Indra; Wiendarlina, Ike Yulia (Fakultas Matematika dan ilmu pengetahuan Alam. Universitas Pakuan.)
Herbs and spices are very important and useful as therapeutic agent against typhoid fever. Increasing multidrug resistance of pathogens forces to find alternative compounds for treatment of these infectious diseases. Garlic contained volatile oil and alisin which containing sulfur. The present study was to evaluate the antibacterial potential of fresh and powder of garlic (Allium sativum L.) extracts against the bacterial pathogens Salmonella typhi and describes the phytochemical analysis. Methods: In the present study the antimicrobial potency of fresh and powder of garlic was carried out by disc diffusion and dilution method against Salmonella typhi bacterial and qualitatively tested for the presence of chemical constituents for the identification of flavonoids, saponins, tannins, alkaloids by the method described previously. The results of the present study showed the fresh and powder of garlic (Allium sativum L.) same as susceptible for Salmonella typhi. The (minimum inhibitory concentration) MIC of fresh of garlic at 10% and the powder of garlic at 8%. The most effective concentration of fresh and powder of garlic for Salmonella typhi is 90 %. Phytochemical screening of ethanol extract of Allium sativum L revealed the presence of various bioactive components of flavonoids, saponins, tannins and alkaloids were the most prominent. Key words : Allium sativum, Antibacterial, Salmonella typhi